An Assessment of the Hydrogeology and Hydrochemistry of the main Aquifers in Darnah Region, NE. Libya - M. Salloum, Fathi (Scientific Journal of University of Benghazi, 2026)
The aim of this paper is to evaluate the Hydrogeology and hydrochemistry in the main aquifer in Darnah region, the Eocene Apollonia and Darnah formations, which are exposed only in the northwest center, and consists mainly of fossiliferous limestone; perched aquifers from the Tertiary Oligocene ) Al Baydah and Al Abraq Formations( and the Miocene Al Faidiyah Formation( in which the limestone are contributing to the water resources in the eastern side, Martubah area. Most of the southern part of the study area is covered by the Neogene rocks of Al Faidiyah Formation. A number of chemical analyses from previous consultant studies in the Darnah region were reviewed and analyzed. In addition, more samples from different localities were collected during June 2006. Some of these samples are from pumped wells and others from natural flowing springs. The newly performed analyses show a reasonable agreement with the previous data whenever cross-checking was possible. The salinity of the main aquifer in the western part of the study area shows a quite regular increasing trend west to east and north to south (Fig. 4 and Fig. 8), the water quality trend is matching closely to the groundwater flow direction. Many trials have been performed to estimate the recharge of aquifers in the area. The climate of the study area has been discussed in order to understand the relation and link with estimation of aquifer characteristics in terms of recharge and water balance, these parameters are important for long term water management for Darnah region. Climatic data were identify the environment and further more classify the area in the range of weather humid up to Desertic class. Water resources have been also discussed, discharge measurements of springs were evaluated through the last decades with respect with water wellfields in the upper stream.